Sharia Economics at the Micro Level: Application of Transaction Principles among Street Vendors - Putri Dewi, Azizah; Wargo; Abidin, Zaenal (Journal of Economics and Social Sciences (JESS), 2025)
This study examines the implementation of Islamic economic principles in street vendors’ (PKL) transactions at Pasar Angso Duo, Jambi City, employing a qualitative approach through in-depth interviews, participatory observation, and document analysis. The findings reveal that the application of Sharia principles occurs in a partial and pragmatic manner, relying more on personal ethics, customer trust, and traditional market culture than on formal fiqh muamalah understanding. Principles such as price transparency, justice (‘adl), the prohibition of riba, and the avoidance of gharar are observed in practice, albeit without the use of formal Sharia terminology. The bargaining mechanism plays a pivotal role as a natural medium for realizing the principle of an-tarāḍin (mutual consent), while challenges such as limited formal understanding, economic pressures, and minimal institutional guidance act as inhibiting factors. This study contributes to the literature by demonstrating that the core values of Islamic economics can organically emerge within an informal sector that operates with minimal regulation. The implications underscore the need for culturally grounded and participatory strategies to strengthen Sharia-compliant economic practices, including contextualized education, accessible Islamic microfinance, and adaptive regulations attuned to the dynamics of traditional markets, to sustain the core values of Sharia while enhancing the welfare of street vendors